Effects of ice cover on the diel behaviour and ventilation rate of juvenile brown trout. (11th August 2013) - Watz, Johan; Bergman, Eva; Piccolo, John J.; Greenberg, Larry
Summary: Winter ice conditions in boreal streams are highly variable, and behavioural responses by fish to river ice may affect overwinter survival rates. One type of ice, surface ice, stabilises water temperatures, reduces instream light levels and may provide overhead cover. Because surface ice is believed to afford protection against endothermic predators, we predicted that metabolic costs associated with vigilance would be lower under surface ice than in areas lacking surface ice. This potentially favourable effect of ice cover was tested by observing ventilation rates of juvenile brown trout ( Salmo trutta ) in a laboratory stream at dawn, during the day and at night in the presence and absence of real, light‐permeable surface ice. Further, we offered trout drifting prey during daylight to test whether ice cover increased daytime foraging activity. Ice cover reduced ventilation rates during the day, but not at night or dawn. Moreover, fish made more daytime foraging attempts in the presence of ice cover than in its absence. We suggest that the most plausible explanation for these results is that fish experience a reduced perceived predation risk under surface ice.